THE ROLE OF ETHNOPEDAGOGY IN THE FORMATION OF YOUTH NATIONAL IDENTITY - Pulatova, Zilola (Журнал иностранных языков и лингвистики, 2023)
This article deals with the role of ethnopedagogical knowledge and experience, i.e. traditions, culture and samples of folk oral art, which form their basis, in the formation of the national identity of young people.